Pengaruh Citra Merek dan Kualitas Produk Terhadap Keputusan Pembelian Simcard Telkomsel (Surgey Pengguna Telkomsel di Kahupaten Karawang) - Novia Nur Ardila; Reminta Lumban Batu (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study is to find out, analyze, and explain the describe of each variable, the amount of influence, partially and simultaneously, the brand image and product quality have on purchasing decisions on Telkomsel simcards in Karawang Regency. The research was conducted by distributing questionnaires to Telkomsel simcard users. The samples in this study totaled 130 samples, with sampling using the probability sampling method through the area sampling technique. The analysis method used for this study is SEM-PLS and the software to process data using SmartPLS 3. The results of the analysis that has been carried out in this study show that brand image has a positive and significant effect on purchasing decisions with t-statistics values (2.655) and P values (0.008). Product quality has a positive and significant effect on purchasing decisions with t-statistics (7,248) and P-values (0.000). Brand image and product quality simultaneously have a positive and significant effect on purchasing decisions with a sig. value of (0.000) < α (0.05) and F-count (109.348) > F table (3.08).